Modelo de Calidad del Aire para Bogotá - Siabato Vaca, Willington Libardo; Sánchez Ipia, Alber Hamersson; Cely Pulido, John William (Ingeniería, 2001)
Through years, mank ind has spread pollutants in the atmosphere. Big cities and their factories produce air contaminants, this substances can reach humans lungs and make people sick. these is a problem that has been getting worse since the in dustrial revolution and nowadays one of the main topics of many international meetings. This article describes one of the efforts that Universidad Distrital Francisco José de Caldas has made about this problem in Bogotá D.C. Colombia. When an atmospheric station measures the concentration of pollutants in the air, these measures do not select the source (factories, cars, airports, human emissions and natural particles). All kinds of the Gaussian plume model (punctual, linear) allow an approach to the quantification of this sources separately. This permits the control of this sources and save time and efforts for the contamination control.The results of this work imply a substantial improvement in the analysis process of the information gathered by each one of the stations. The raised model presents as results when crossing it with geographical infor mation the precise description of the behavior of the concentrations emitted by a group of chimneys for any group of data that have been gathered in certain date and hour. Starting from this spatial information it is compared with the established norms for the control of maximum emissions like Resolution 391 of 2001 of the DAMA. This way, it will be able to determinate in a very simple and agile way if the norm is been transgressing and the areas of the city where this flaw is happening.